Feedback as a means to improve clinical competencies: Registrars’ perceptions of the quality of feedback provided by consultants in an academic hospital setting - Chauntelle Bagwandeen; Veena Singaram (South African Medical Association, 2016)
Background. The training of novices, in any field, to achieve the optimum state of cognitive, clinical, technical and professional development requires a variety of teaching methodologies, including the process of feedback. Feedback is defined as a process where the desired standard of proficiency in a task has already been established and communicated to the student before gaps in performing the task or in the level of knowledge are identified. The process of feedback has often been evaluated and has consistently revealed students’ dissatisfaction with the amount and type of feedback they receive in their clinical and postgraduate training, as they perceive it to be inadequate, inappropriate or non-existent. Objectives. To investigate the perceptions of the quality of feedback received by a diverse, heterogeneous population of registrars in postgraduate training at an academic hospital. Methods. A study was conducted using a questionnaire to determine the perceptions of all registrars in the six major clinical training programmes with regard to the quality, efficacy and effectiveness of feedback received during clinical training. Descriptive statistics were used to interpret the responses of the registrars, with mean values being calculated. Results. Perceptions of the quality of feedback received differed across disciplines. Overall, the registrars rated the feedback they received as poor. The majority (51.4%) reported that both formal and informal feedback was only sometimes, even rarely, received during all encounters with consultants. Others (51.3%) felt that the feedback received was unacceptable, and did not perceive it to be based on concrete observations of performance. The proficiency of consultants in giving feedback was scored as unacceptable by 64.8% of registrars. Conclusion. Registrars in training regard feedback as an essential component of their postgraduate medical education and as an important component of achieving clinical competence. More formalised processes need to be implemented. The majority of registrars agreed that consultants required training in providing feedback effectively.